Opaque Theism and Divine Testimony - Wielenberg, Erik J. (TheoLogica, 2025)
A much-discussed objection to skeptical theism is that skeptical theism implies that divine testimony cannot provide us with knowledge. Here I argue that it is not skeptical theism that raises doubts about the trustworthiness of divine testimony; rather, the vast amount of inscrutable evil in our world together with God's track record of deception is the source of the trouble. I draw on that insight to develop further my divine deception argument (Wielenberg 2014). The argument I will defend goes roughly like this: There is a lot of inscrutable evil in the world and the Christian God has a track record of being deceptive about future events. Therefore, divine testimony regarding future events is not a source of knowledge that such events will occur.